Chemical composition, antimicrobial, and antioxidant properties of essential oils from Artemisia herba-alba asso. and Artemisia huguetii caball. from Morocco: in vitro and in silico evaluation - El Ouardi, Mohamed; Drioiche, Aziz; El Makhoukhi, Fadoua; Mabrouki, Jamal; Hakmi, Mohammed; Al kamaly, Omkulthom; A. Alsfouk, Bshra; Eddamsyry, Brahim; Khamar, Hamid; Zair, Touriya; Alaoui El Belghiti, Mohammed (Frontiers in Chemistry, 2024)
This study aims to comprehensively characterize the chemical composition of Artemisia essential oils and evaluate their antibacterial and antioxidant properties using In vitro experiments and in silico simulations. In order to do this, we gathered samples of Artemisia herba-alba Asso. from Boulemane and Ifrane in Morocco, as well as Artemisia huguetii Caball. from Tata. These samples were obtained from the Central Middle Atlas and the Western Anti-Atlas areas, and the essential oils were extracted using hydrodistillation. The composition was determined by the use of gas chromatography-mass spectrometry (GC-MS) analysis. The findings indicated that the extraction yields exhibit variation based on the geographic source, with values ranging from 1.54% to 2.78%. The GC-MS study demonstrates variations in chemical composition across different species of Artemisia and different geographical locations, notably distinguished by the prevalence of oxygenated monoterpenes. Every species possesses a unique chemical composition. The Artemisia oil obtained in Boulemane is notably abundant in thujone, whilst the oil from Ifrane is mostly characterized by camphor. On the other hand, the oil from Tata is mainly made of camphor and thujone. The essential oils had greater antifungal efficacy than antibacterial efficacy, displaying both bactericidal and fungicidal effects. The Enterobacter cloacae strains exhibited high sensitivity to the different essential oils, with minimum inhibitory concentrations (MIC) of around 12.5 mg/mL. The essential oil of A. herba-alba Asso. obtained in Boulemane had the greatest degree of antioxidant activity, effectively inhibiting DPPH at a concentration of 13.501 μg/mL. By employing computer models, we were able to predict that the primary compounds would exhibit potent antibacterial and antioxidant properties. These compounds have favorable ADMET qualities in terms of blood-brain barrier permeability, gastrointestinal absorption, and skin penetration. The molecular docking investigation elucidated the intricate connections between the crucial chemicals (davanone, eucalyptol, camphor, and thujone) and the target proteins responsible for the biological functions (NADPH-dependent catalase and dihydrofolate reductase). The stability of the protein-ligand complexes was validated by molecular dynamics, with a particular emphasis on the significant influence of davanone.